#52 In-silico studies of some novel benzotriazole derivatives against the NNIBP of HIV-1 RT - Maiti, Nigam Jyoti; Ganguly, Swastika (Journal of Pharmaceutical Chemistry, 2022)
Benzotriazole is a heterocyclic molecule that has many biological actions such as antibacterial, antifungal, anticancer, anti-inflammatory, analgesic, antimalarial, and antitubercular activity. The objective of this work is to report the study of a series of designed benzotriazole derivatives that have been examined for their molecular docking in the non-nucleoside inhibitory binding pocket (Non-nucleoside reverse transcriptase inhibitors binding pocket) of HIV-1 RT. The methodology consists of a series of eight compounds (2a-h) which, based on the pharmacophoric group requirements of the NNRTIs, have been designed and drawn using ChemDraw and docked against nonnucleoside inhibitory binding pocket (NNIBP) of HIV-1 RT (PDB ID:1RT2) receptor using AutoDock Vina software. Binding mode results showed that among seven designed compounds, compound-2a1-(4-chlorophenyl)-2-(perbromo-2H-benzo[d][1,2,3]triazol-2-yl)ethan-1-ol gave the highest docking score of -9.3 Kcal/mole when compared to the standard Nevirapine. It also exhibited hydrogen bond interactions with PRO236 and LYS103 amino acids of the NNIBP of 1RT2. It is therefore concluded that compound 2a can be used as a lead for preparing further synthetic derivatives which can be used for docking studies in the NNIBP of HIV-1- RT.